The behavior of a co-flow structure to screen projects in a product pipeline - Figueiredo, Paulo Soares (2016)
In many situations, System Dynamics modelers have to capture attributes of items tracked in an aging chain by means of a co-flow. This study presents an application of co-flows in aging chains: A co-flow that enables the process of screening, i.e. the process of either terminating or approving projects. The article is the fifth in a series of articles about the model. An application to Product Pipeline Management (PPM) is developed. A two-stage product development pipeline was modeled with a co-flow structure that tracks the number of projects and the related net present value of payoff. Managers at each stage must decide on capacity utilization and thresholds for minimum value of projects. Simulation results illustrate that screening can eliminate the backlog bullwhip effect in the pipeline.